Highly active nanostructured CoS2/CoS heterojunction electrocatalysts for aqueous polysulfide/iodide redox flow batteries - Dui Ma (Nature Portfolio, 2019)
Polysulfide/iodide redox flow batteries are promising due to low cost and high-solubility components, but are limited by energy efficiency and power density. Here the authors fabricate heterojunction electrocatalysts to achieve improved performance in a polysulfide/iodide redox flow battery.